2014
DOI: 10.1111/famp.12086
|View full text |Cite
|
Sign up to set email alerts
|

The Biobehavioral Family Model: Testing Social Support as an Additional Exogenous Variable

Abstract: This study tests the inclusion of social support as a distinct exogenous variable in the Biobehavioral Family Model (BBFM). The BBFM is a biopsychosocial approach to health that proposes that biobehavioral reactivity (anxiety and depression) mediates the relationship between family emotional climate and disease activity. Data for this study included married, English-speaking adult participants (n = 1,321; 55% female; M age = 45.2 years) from the National Comorbidity Survey Replication, a nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
3
28
1
3
Order By: Relevance
“…More explicitly, we propose that a warm family emotional climate, secure internal attachment models within the pregnant mother, and good relationship quality between the pregnant mother and an intimate partner, and between the pregnant mother and other family members, will buffer the effect of external socioeconomic stress on the pregnant mother (Woods, Priest, & Roush, 2014). In contrast, hostile family emotional climate, insecure maternal attachment, compromised partner and family relationships will fail to buffer, and even exacerbate, the effect of external stressors on the pregnant mother.…”
Section: The Integration Of the Bbfm Into Wright's Socio-psycho-biolomentioning
confidence: 99%
“…More explicitly, we propose that a warm family emotional climate, secure internal attachment models within the pregnant mother, and good relationship quality between the pregnant mother and an intimate partner, and between the pregnant mother and other family members, will buffer the effect of external socioeconomic stress on the pregnant mother (Woods, Priest, & Roush, 2014). In contrast, hostile family emotional climate, insecure maternal attachment, compromised partner and family relationships will fail to buffer, and even exacerbate, the effect of external stressors on the pregnant mother.…”
Section: The Integration Of the Bbfm Into Wright's Socio-psycho-biolomentioning
confidence: 99%
“…The Biobehavioral Family Model (BBFM; Wood, ) is a biopsychosocial model of health (e.g., Lim, Wood, & Miller, ; Lim, Wood, Miller, & Simmens, ; Priest & Woods, ; Priest et al., ; Woods & Denton, ; Woods, Priest, & Roush, ). The BBFM examines how negative family emotional climate contributes to individual family members experiencing greater biobehavioral reactivity (i.e., depression, anxiety, and psychophysiological stress) resulting in increased disease activity (i.e., chronic health conditions).…”
Section: The Biobehavioral Family Modelmentioning
confidence: 99%
“…The BBFM examines how negative family emotional climate contributes to individual family members experiencing greater biobehavioral reactivity (i.e., depression, anxiety, and psychophysiological stress) resulting in increased disease activity (i.e., chronic health conditions). Originally developed to explain associations between family relationships and health for children (Wood, ), recent research has shown the model's utility in examining association between family relationships and health for adults (e.g., Priest & Woods, ; Priest et al., ; Woods & Denton, ; Woods et al., ).…”
Section: The Biobehavioral Family Modelmentioning
confidence: 99%
See 2 more Smart Citations